VARIATION AND NORMALIZATION OF THE POLISH LANGUAGE IN THE OLD PRINTS FROM THE FIRST HALF OF THE 16TH CENTURY - MIGDAŁ, JOLANTA (Slavia Occidentalis, 2020)
The article presents normalization of the Polish literary language in prints from the first half of the 16th century. It was a breakthrough period for the normalization process in which the activities aimed at limiting the variation of language forms were intensified. The linguistic analysis presented here focuses on two groups of sixteen-century texts: Polish palaeotypes, that is the prints from Cracow from the years 1521–1522 as well as on the writings of Andrzej Glaber of Kobylin published in the years 1535–1539 in the Cracow publishing house of Florian Ungler and his wife Helena where he performed various functions: of an author, translator and editorpublisher.The observation and study of variance of language forms and its limitation enables us not only to determine the degree of normalization of the Polish language in particular periods, but also to characterize the attitude to standards of sixteen-century publishers of Polish books. On the basis of the comparison of normalization of Polish in palaeotypes from the years 1521–1522 and in the works of Andrzej Glaber from the years 1535–1539 we can conclude that the first half of the 16th century was characterized by particular standards. It is difficult to notice an apparent continuity of the normalization tradition. Nevertheless, we can discern in this period a developing progressive trend in the normalization of the Polish literary language which quickly became widespread. The group of progressive normalizers definitely includes: the anonymous editor of Żywot Pana Jezu Krysta, printed in the publishing house of Hieronim Wietor, Jan from Koszyczki, Hieronim from Wieluń (Spiczyński) and Andrzej Glaber. In the later period also Jan Seklucjan and Stanisław Murzynowski joined this group, the polemicists who broke the old linguistic traditions of Jan Sandecki-Malecki. Nowadays, on the basis of the findings of numerous historical-linguistic analyses, the victory of this progressive option is quite apparent..